How to succeed in interviews - Mitra, A. K. (New Delhi, 1997)
You've got the interview - now how will you get the job? How to Succeed in any Interview will show you how to present yourself as the best candidate for the job, using proven tips, advice and techniques from the experts to guide you through exactly what interviewers want to see and what impresses them most. Present yourself in the best possible light - every time Understand what impresses interviewers the most Win the job before, during and after the interview Learn how to show yourself in the best possible light and maximise your chances of making a brilliant impression and getting that job.
Keywords: Employment interviewing; Interviewing